Nutrient Composition of Stiff Porridge made from Carrots and Eggplant Flour and its Nutritional Benefit to Elderly. - Ozioma C. Azubuike; Adaeze L. Nwaigwe; Uju B. Ejinkeonye; Glory M. Nwakpadolu (International Journal of Home Economics, Hospitality and Allied Research)
This study assessed the nutritional composition of stiff porridge made from carrots and eggplant flour and its nutritional benefit to elderly. The result revealed that significant differences existed in the proximate, mineral, vitamin and sensory attributes of the samples with moisture content of the stiff porridge ranging from 33.78 to 35.00%. Sample A (Stiff porridge from 100% eggplant) had the highest moisture content (38.00%) whereas sample C (Stiff porridge from 50% eggplant and 50% carrot) had the lowest moisture. Sample A (Stiff porridge from 100% eggplant) had the highest the calcium content (50.00%), Sample A (Stiff porridge from 100% eggplant) had the highest potassium (129.14 mg/100g) while sample C (Stiff porridge from 50% eggplant and 50% carrot) had the lowest value of potassium (98.15 mg/100g). However, Sample C (Stiff porridge from 50% eggplant and 50% carrot) had the highest mean score for general acceptability (7.20) whereas sample A (Stiff porridge from 100% eggplant) had the least mean score (6.00). This study concluded that the potentials of eggplant and carrot as useful alternatives in the production of stiff porridge for healthy family feeding in Umuahia North Local Government Area in Abia State. Based on this study, the following recommendations are made: Utilization of 100% eggplant in stiff porridge production is recommended especially to individuals that are mineral deficient since it had increased mineral content, in addition to proximate composition. The stiff porridges should not be kept for quite long before consumption since it possesses high moisture. Sensitization of the general populace on the potentials of eggplant and carrot blends in the production of stiff porridge will contribute to enhancing their utilization and health benefits especially to the elderly.